Analisis Kapasitas Saluran Drainase Berdasarkan Analisis Curah Hujan Di Jalan Rahayu Pasar Vii Tembung - Najwa, Wardatun; Simanjuntak, Rizky; Gulo, Kanisius Delvin S; Prayogo, Wisnu; Harahap, Rumilla (CV. SINAR HOWUHOWU, 2026)
The rapid population growth, projected to reach 151,340 people by 2026, significantly increases the burden on urban infrastructure. This study aims to evaluate the adequacy of the existing drainage channel capacity in coping with a 50-year return period rainfall of 3,861 mm. The methodology employed is field research using a quantitative approach through direct observation and measurement at the study site. Hydrological analysis was conducted by accounting for an evapotranspiration factor of 60% to obtain accurate runoff values. The results indicate that water flow efficiency is severely hindered by sediment accumulation, with the highest sediment volume reaching 728.26 m³ and a thickness of 0.41 m. Technically, the current channel dimensions are only safe for a return period of ≤10 years. Therefore, strategic measures are required, including channel redesign and periodic sediment dredging management, to ensure long-term safety and minimize flood risks for the community.